Anterior Cruciate Ligament Regeneration in an 8-Year-Old Patient - Arts, S. J.; Polak, M. P. J.; Janssen, R. P. A. (The Journal of Knee Surgery Reports, 2015)
Ruptured anterior cruciate ligaments (ACL) have doubtful healing potential. This might be better in younger patients. Therefore, treatment of an ACL rupture in the skeletally immature patient knows several strategies. We report the case of an 8-year-old, skeletally immature patient with a midsubstance-ruptured ACL at physical exam and magnetic resonance imaging (MRI). Conservative treatment with a brace led to a stable knee with regeneration of the ACL on both the physical examination and MRI after 5 years. Nevertheless, further research will be necessary to gain better understanding about the biology and healing potential of the ACL.
Keywords: skeletally immature; anterior cruciate ligament; regeneration; children; knee